Migrants with Disabilities [MWDs], Mental Health, and Exclusion in COVID-19 Palliative in South Africa : Legislations on Disabilities - Umoh, Samuel Uwem; Matoane, Matshepo Catherine (INKLUSI, 2024)
The paper discusses the challenges of migrants with disabilities (MWDs) during COVID-19 and how government policies either amplify or aggravates their challenges in South Africa. This study also examined current disability legislation and COVID-19 policies on MWDs. The study is a qualitative study based on interviews with seven participants. Data were analyzed by thematic analysis. Findings suggest that MWDs struggles with mental health, exclusion from health care, COVID-19 palliative and social welfare. The paper argues that South Africa has failed to develop and execute relevant policies and strategies to assist MWDs. This is evidenced in insufficient government policy on the inclusion of MWDs in COVID-19. The paper suggests that the South African government and disaster management plans should improve policies and services provided to MWDs. It is also suggested that MWDs should enjoy human rights and be treated equally. This necessitates a review of current capacities and strengthening of disabilities legislation specific to MWDs. Penelitian ini membahas tantangan yang dihadapi oleh migran penyandang disabilitas (MWD) selama pandemi COVID-19 dan bagaimana kebijakan pemerintah dapat memperburuk atau memperparah tantangan mereka di Afrika Selatan. Studi ini juga meneliti undang-undang disabilitas saat ini dan kebijakan COVID-19 terkait MWD. Penelitian ini merupakan studi kualitatif berdasarkan wawancara dengan tujuh partisipan. Data dianalisis menggunakan analisis tematik. Temuan menunjukkan bahwa MWD mengalami masalah kesehatan mental, pengucilan dari layanan kesehatan, bantuan COVID-19, dan kesejahteraan sosial. Makalah ini berpendapat bahwa Afrika Selatan tidak berhasil mengembangkan dan melaksanakan kebijakan serta strategi yang relevan untuk membantu MWD. Hal ini terbukti dari kebijakan pemerintah yang kurang memadai dalam mengikutsertakan MWD selama pandemi COVID-19. Penelitian ini menyarankan agar pemerintah Afrika Selatan dan rencana manajemen bencana harus meningkatkan kebijakan dan layanan yang disediakan untuk MWD. Juga disarankan agar MWD menikmati hak asasi manusia dan diperlakukan secara setara. Hal ini memerlukan peninjauan kapasitas saat ini dan penguatan undang-undang disabilitas yang spesifik untuk MWD.